2015
DOI: 10.18191/2015-08-2-025
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and molecular detection of Salmonella enterica serogroups and spvC virulence gene in raw and processed meats from selected wet markets in Metro Manila, Philippines

Abstract: Abstract-A simple and specific detection method for Salmonella enterica was applied to determine its incidence in raw and processed meats purchased from selected wet markets in Metro Manila, Philippines. A total of 320 raw and processed meat samples were analysed for the presence of S. enterica and S. enterica possessing spvC gene of the virulence plasmid. Polymerase chain reaction (PCR) revealed that 30.63% (98/320) were positive for S. enterica and 2.81% (9/98) of S. enterica-positive samples were also posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…studies in Metro Manila demonstrated that Salmonella serogroup O:3 was the most dominant serogroup detected in raw and processed meat (78.57%) from wet markets [13], and slaughtered swine (75%) from slaughterhouses [15]. However, Ng & Rivera [14] found that serogroup O:4 (73%) was the most frequently isolated serogroup in slaughtered swine in abattoirs followed by serogroup O:3 (24%).…”
Section: Plos Onementioning
confidence: 99%
See 4 more Smart Citations
“…studies in Metro Manila demonstrated that Salmonella serogroup O:3 was the most dominant serogroup detected in raw and processed meat (78.57%) from wet markets [13], and slaughtered swine (75%) from slaughterhouses [15]. However, Ng & Rivera [14] found that serogroup O:4 (73%) was the most frequently isolated serogroup in slaughtered swine in abattoirs followed by serogroup O:3 (24%).…”
Section: Plos Onementioning
confidence: 99%
“…Quality of the market sanitation and practices were ranked on an ordinal scale of five values ranging from poor to very good (S1 Appendix). [ [13][14]. Briefly, 25 g meat sample was aseptically manually homogenized and inoculated into 225 ml buffered peptone water (BPW; BD Diagnostics System Difco TM USA) in a sterile bottle.…”
Section: Sample Collectionmentioning
confidence: 99%
See 3 more Smart Citations